Perkembangan Pemikiran Keagamaan Remaja Perspektif Psikologi Agama di MTS AL-MA’MUR - Mailani, Putri; Ramadhani, Alya; Aulia, Najwa Fadhila; Hikmah, Nurul; Batubara, Noor Azida (Jurnal Pendidikan Tambusai, 2026)
This study examines the development of adolescents' religious thinking from the perspective of psychology of religion at MTs Al-Ma’mur Bekasi, where challenges such as puberty, social media, and low economic backgrounds threaten religious conviction stability. The objectives are to analyze religious character building strategies, identify supporting-inhibiting factors, and recommend adaptive models. It employs a qualitative descriptive approach with in-depth interviews. The population includes the principal, 23 teachers, and 100 students in grades VII-IX; purposive snowball sampling targeted key informants. Instruments comprised semi-structured interview guides, observation sheets, and documentation; data analysis used Miles and Huberman's thematic technique. Results reveal effective strategies like congregational prayer habituation in public mosques, student leadership roles, and three-pillar collaboration (school, family, community), despite social media barriers. The conclusion recommends mosque-based habit-building integration for similar madrasahs to enhance adolescent religious resilience.